2017
DOI: 10.1111/cbdd.13088
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic conformationally constrained spiro carbocyclic 2,6‐diketopiperazine‐1‐acetohydroxamic acid analogues as trypanocidal and leishmanicidal agents: An extended SAR study

Abstract: We have previously described a number of lipophilic conformationally constrained spiro carbocyclic 2,6-diketopiperazine (2,6-DKP)-1-acetohydroxamic acids as potent antitrypanosomal agents. In this report, we extend the SAR analysis in this class of compounds with respect to in vitro growth inhibition of Trypanosoma and Leishmania parasites. Introduction of bulky hydrophobic substituents at the vicinal position of the basic nitrogen atom in the spiro carbocyclic 2,6-DKP ring system can provide analogues which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Rational designtheoretical calculations Previous studies by our group have resulted in compounds carrying metal chelating moieties that demonstrated a highly promising inhibition capacity against either pathogenic viruses, including influenza and HCV, 56 or parasites of the Trypanosoma genus. 57,58 The two above-mentioned series of analogues, although structurally diverse, were based on rational incorporation of metal chelating moieties on scaffolds with pronounced drug-likeness, such as the combination of flutimide with the indole system (I) or incorporation of the acetohydroxamic acid moiety on a 2,6-diketopiperazine (2,6-DKP) scaffold (II) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Rational designtheoretical calculations Previous studies by our group have resulted in compounds carrying metal chelating moieties that demonstrated a highly promising inhibition capacity against either pathogenic viruses, including influenza and HCV, 56 or parasites of the Trypanosoma genus. 57,58 The two above-mentioned series of analogues, although structurally diverse, were based on rational incorporation of metal chelating moieties on scaffolds with pronounced drug-likeness, such as the combination of flutimide with the indole system (I) or incorporation of the acetohydroxamic acid moiety on a 2,6-diketopiperazine (2,6-DKP) scaffold (II) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, compound 15 displays itself as a promising starting point for further development of potent agents against Leismania infantum parasites. One important additional aspect that will have to be evaluated in further development of this hit compound is also to determine its influence on the mammalian cells [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lancet 391, 144-154. [6] European Medicines Agency recommends fexinidazole, the first all-oral treatment for sleeping sickness. https://www.dndi.org/2018/media-centre/pressreleases/).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these derivatives (III-IV, Figure 1) showed submicromolar trypanocidal activities in vitro; in particular the adamantane analogue III (IC 50 =0.33 μΜ) gave 400-and 21-fold increases in antitrypanosome potency compared to amantadine and rimantadine, respectively. 6 In our earlier works we communicated the trypanocidal properties of some nitrogen-containing adamantane derivatives (amines or not). 7,8 Among them, compounds V-VII (Figure 1) possessed considerable activities in vitro against T. brucei.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation